The effect of distant metastases sites on survival in de novo stage-IV breast cancer: A SEER database analysis - San-Gang Wu; Hui Li; Li-Ying Tang; Jia-Yuan Sun; Wen-Wen Zhang; Feng-Yan Li; Yong-Xiong Chen; Zhen-Yu He (Tumor Biology)
To investigate the effect of distant metastases sites on survival in patients with de novo stage-IV breast cancer. From 2010 to 2013, patients with a diagnosis of de novo stage-IV breast cancer were identified using the Surveillance, Epidemiology, and End Results database. Univariate and multivariate Cox regression analyses were performed to analyze the effect of distant metastases sites on breast cancer–specific survival and overall survival. A total of 7575 patients were identified. The most common metastatic sites were bone, followed by lung, liver, and brain. Patients with hormone receptor+/human epidermal growth factor receptor 2− and hormone receptor+/human epidermal growth factor receptor 2+ status were more prone to bone metastases. Lung and brain metastases were common in hormone receptor−/human epidermal growth factor receptor 2+ and hormone receptor−/human epidermal growth factor receptor 2− subtypes, and patients with hormone receptor+/ human epidermal growth factor receptor 2+ and hormone receptor−/human epidermal growth factor receptor 2+ subtypes were more prone to liver metastases. Patients with liver and brain metastases had unfavorable prognosis for breast cancer–specific survival and overall survival, whereas bone and lung metastases had no effect on patient survival in multivariate analyses. The hormone receptor−/human epidermal growth factor receptor 2− subtype conferred a significantly poorer outcome in terms of breast cancer–specific survival and overall survival. hormone receptor+/human epidermal growth factor receptor 2+ disease was associated with the best prognosis in terms of breast cancer–specific survival and overall survival. Patients with liver and brain metastases were more likely to experience poor prognosis for breast cancer–specific survival and overall survival by various breast cancer subtypes. Distant metastases sites have differential impact on clinical outcomes in stage-IV breast cancer. Follow-up screening for brain and liver metastases might be effective in improving breast cancer–specific survival and overall survival.